Analisis Nitrat dan Fosfat Terhadap Kesuburan Perairan Muara Sungai Bodri - Mishbach, Imam; Muhammad Zainuri, Muhammad; Lolita Tuhumena, Lolita; Gea, Liyatin; Agamawan, Lalu Panji Imam; Hamuna, Baigo (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
Nitrate (NO3-) and phosphate (PO4^3-) are two compounds that have a significant impact on aquatic ecosystems. Nitrate, which consists of nitrogen and oxygen, has both natural and anthropogenic sources. Meanwhile, phosphate, which contains phosphorus and oxygen, is an important component in plant nutrition. This is a problem in the Bodri River Estuary, Kendal. The objective of this study was to assess the nitrate and phosphate content and their distribution pattern. The research was conducted based on observation method with spatio-temporal approach. A total of 9 research stations and sampling times were June 30, September 1 and October 27, 2018. Nitrate and phosphate content were determined as independent variables. The results showed that the nitrate content at 9 research stations in the Bodri River Estuary was in the range of 0.48-0.8 mg/l and Phosphate 0.8-4.0 mg/l, Kendal Regency was in a fertile/eutrophic condition. The waters of the Bodri River Estuary, Kendal Regency show a high level of fertility or eutrophic.